Presentation: Inderbir Singh’s Textbook of Human Histology with Colour Atlas and Practical Guide / Revised and edited by Neelam Vasudeva, Sabita Mishra. – 7th edition. – Jaypee Brothers Medical Publishers, 2014. – 440 p. - journal "Morphologia", Editorial office (Морфологія / Morphologia / Morfologìâ, 2014)
Dear readers! In this edition of the magazine, the editorial board introduces the textbook on human histology, Inderber Singh, the seventh edition, revised and edited by Nilam Vasudeva and Sabit Mishra. It came out with a color atlas containing over 80 slides and allows the reader to get acquainted with the basics of histology.